Seed Hubs for East and Southern Africa: Mobilizing knowledge and resources for resilient seed systems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Through an iterative process of consultations, including with lead PGR and seed organizations in East and Southern Africa, a detailed document was produced outlining the key features of the proposed sub-hubs, which has been acknowledged/endorsed by leading national organizations in Kenya, South Africa, Tanzania, Uganda, Zambia, and Zimbabwe.